2020
DOI: 10.3389/fpsyt.2020.00843
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine Attenuates Schizophrenia-Like Behaviors and Demyelination in a MK-801–Induced Mouse Model of Schizophrenia

Abstract: Brain demyelination is possibly one of the main pathological factors involved in schizophrenia, and targeting on myelination may be a useful strategy for schizophrenia treatment. Quetiapine, a widely used atypical antipsychotic drug for schizophrenia treatment, has been reported to have neuroprotective effects on cerebral myelination in a demyelination animal model. The objective of the present study was to evaluate the effect and underlying neuroprotective mechanism of quetiapine on the schizophrenia-like beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…The most important finding of our multicohort study is the observation that quetiapine was able to normalise the PPI disturbances in adult male offspring in the MIA model. As presented in the literature, this atypical antipsychotic has shown efficacy in treating positive and negative symptoms as well as cognitive impairment in schizophrenia patients [ 88 ]. Moreover, consistent with our data, quetiapine attenuated schizophrenia-like behaviours, including not only sensorimotor gating deficits but also hyperactivity and memory impairment, in the MK-801-treated mouse model [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important finding of our multicohort study is the observation that quetiapine was able to normalise the PPI disturbances in adult male offspring in the MIA model. As presented in the literature, this atypical antipsychotic has shown efficacy in treating positive and negative symptoms as well as cognitive impairment in schizophrenia patients [ 88 ]. Moreover, consistent with our data, quetiapine attenuated schizophrenia-like behaviours, including not only sensorimotor gating deficits but also hyperactivity and memory impairment, in the MK-801-treated mouse model [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…As presented in the literature, this atypical antipsychotic has shown efficacy in treating positive and negative symptoms as well as cognitive impairment in schizophrenia patients [ 88 ]. Moreover, consistent with our data, quetiapine attenuated schizophrenia-like behaviours, including not only sensorimotor gating deficits but also hyperactivity and memory impairment, in the MK-801-treated mouse model [ 88 ]. Therefore, the present research reaffirmed the face and construct validity of the use of MIA in modelling schizophrenia-like symptoms and the predictive validity of quetiapine administration.…”
Section: Discussionmentioning
confidence: 99%
“…Quetiapine was found to improve the decrease in BDNF-positive cells in the basolateral amygdala and hippocampus of transgenic models of mice with Alzheimer's disease (Tempier et al, 2013) through its modulating effects on neuroprotective factors such as reducing demyelination and increasing BDNF (He et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The stimulatory effects of quetiapine on monoamines such as norepinephrine, dopamine, and serotonin have been reported to be mediated by NMDA/glutamate receptors (Yamamura et al, 2009). Moreover, quetiapine has been shown to reduce schizophrenia-like behaviors, including memory loss, and attenuate BDNF reduction in mice treated with MK-801 (Fumagalli et al, 2004, He et al, 2020. Hence, it can be said that quetiapine affects NMDA receptor activity and modulates the effect of lithium on these receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a better understanding of OLs may aid in the development of SCZ treatment strategies (4,5). Postmortem studies demonstrated a strong association between aberrant OL development and function, as well as demyelination and the pathogenesis of SCZ (6,7). Moreover, histological examinations of the brain revealed a decrease in the number of hippocampal OLs and neurons in patients with SCZ, and the interaction between OLs and neurons was abnormal (8,9).…”
Section: Introductionmentioning
confidence: 99%